Association between ABO Blood Group and Radiographic Findings in Periodontal Disease (Medico Legal Update, 2021)
Background: Periodontal disease is one of the most common diseases in the oral cavity that may beinfluenced by the blood grouping system among individuals. The purpose of this study was to determinewhether there was an association between radiographic findings and ABO blood groups in patients withperiodontal diseases.Material and Method: A prospective study carried out on 200 subjects (99) male and (101) female, aged(18 to 65) who diagnosed clinically with periodontitis who were requested for panoramic and were askedfor ABO blood group and Rh factor determination. The subjects were divided into two groups according tothese findings, as those with (localized chronic periodontitis) and (generalized chronic periodontitis). Theassociation between blood groups and periodontal health were investigated.Result: There is more predominance of the localized chronic periodontitis (60%) of subjects. The distributionperiodontitis with different blood group of the study population (41%, 30%, 20% and, 9%)of blood group Ofollowed by B, A, AB respectively. There is more predominance of subjects with Rh positive group (86.5%)The association between ABO and Rh with age groups and with gender were found to be statistically notsignificant, whilethe association between both localized and generalized chronic periodontitis and Rh factorwas a significant.Conclusion: The association between periodontal diseases and blood group show the high risk people todetermine a perfect treatment plan strategy.